HUBUNGAN PATRON-KLIEN DALAM SISTEM MAWAH KEUBEU DI ACEH BARAT - irma juraida; Rahmah husna Yana; Triyanto Triyanto; Nurlian Nurlian (Jurnal Community, 2020)
This study aims to describe how the patron-client social interaction or relationship between the owner and the buffalo caretakers in Gampong Gunong Mata Ie, Aceh Barat Regency. This study uses the patron-client theory of James Scott using descriptive qualitative research methods with data collection techniques such as observation techniques, and in-depth interviews. The results of this study are a form of interaction or social exchange relationship between patron and client in mawah keubeu: a) material exchange relationship between livestock keepers and livestock owners b) non-material exchange relationships between buffalo breeders and buffalo livestock owners. The patron-client social exchange pattern between buffalo keepers and buffalo owners occurs because of economic inequality. The process of social exchange that occurs in buffalo keepers and buffalo owners is usually very strong and lasts a long time, this is due to the mutual benefit between clients and patrons.